Polyurethane adhesive and preparation method thereof

Through a precise preparation process using high-activity polypropylene oxide-ethylene oxide copolymer polyol and other components, a multifunctional cross-linking network is formed, which solves the performance deficiencies of polyurethane adhesives in extreme temperature and humid environments. This achieves wide-temperature-range bonding stability, resistance to humid heat aging, environmentally friendly flame retardancy, and substrate versatility, meeting the industrial production needs of high-end applications.

CN121293934APending Publication Date: 2026-01-09HUBEI YUTIAN BALI NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511594895.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-03
Publication Date
2026-01-09

AI Technical Summary

Technical Problem

Existing polyurethane adhesives are prone to embrittlement under extreme temperature conditions, have weak resistance to damp heat aging, are difficult to balance environmental protection and flame retardancy, lack versatility in substrate bonding, and have poor stability in preparation processes, making it difficult to meet the multi-dimensional performance requirements of high-end application scenarios.

Method used

It uses a highly active polypropylene oxide-ethylene oxide copolyol, isocyanate mixture, composite chain extender, environmentally friendly catalyst, phosphorus-nitrogen synergistic flame retardant, silane coupling agent and other components, and forms a multifunctional cross-linked network through a precisely controlled preparation process, which ensures wide temperature range performance, resistance to damp heat aging, environmentally friendly flame retardancy and substrate versatility.

Benefits of technology

It achieves an elongation at break of ≥220% at -40℃, a bond strength retention of ≥85% at 120℃, flame retardancy up to UL94V-0 level, the ability to bond to various substrates without pretreatment, and a batch-to-batch performance error of ≤7%, meeting the industrial production requirements of high-end applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121293934A_ABST
    Figure CN121293934A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of high-molecular adhesives, and discloses a polyurethane adhesive which comprises the following components in parts by mass: 1-5 parts of a curing agent, 1-5 parts of a curing agent and 1-5 parts of a curing agent. The high-activity polypropylene oxide-ethylene oxide copolymerized polyol is prepared from the following components in parts by weight: 85 to 125 parts of high-activity polypropylene oxide-ethylene oxide copolymerized polyol, 28 to 40 parts of an isocyanate mixture, 6 to 12 parts of a composite chain extender, 0.3 to 0.8 part of an environment-friendly catalyst, 15 to 25 parts of a phosphorus-nitrogen synergistic flame retardant, 0.8 to 1.5 parts of an anti-aging aid and 1.2 to 2.0 parts of a silane coupling agent. The polyurethane adhesive and the preparation method thereof have the advantages of being high in wide-temperature-range bonding stability, high in damp-heat aging resistance, environment-friendly, flame-retardant, good in base material bonding universality, stable in preparation process and the like; the problems that an existing polyurethane adhesive is poor in wide temperature range performance, poor in damp-heat aging resistance, difficult to give consideration to both environmental protection and flame retardance, insufficient in base material universality and poor in preparation process stability are solved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of high molecular adhesives, in particular to a polyurethane adhesive with wide temperature range bonding stability, high moisture and heat aging resistance and environmental protection and flame retardation, especially suitable for bonding scenes such as automobile lightweight parts (aluminum alloy-carbon fiber composite materials), electronic device packaging (LED drive power supply) and building curtain wall glass-metal keel. BACKGROUND

[0002] Polyurethane adhesives have become an indispensable key material in modern industrial fields (automobiles, electronics, construction, etc.) due to their excellent bonding versatility, mechanical flexibility, and chemical corrosion resistance. However, as downstream applications continue to upgrade their performance requirements, the existing polyurethane adhesives in the prior art have gradually exposed the following core technical pain points, making it difficult to meet the needs of high-end scenarios: Insufficient wide temperature range performance, poor extreme environment adaptability The existing conventional polyurethane adhesives mostly use a single polyoxypropylene polyol as the soft segment, with a high glass transition temperature (Tg) (usually between -30℃ and -20℃), which leads to brittle cracking of the adhesive in low temperature environments (such as northern winter outdoor, automobile cold chain transportation scenarios), a significant decrease in elongation at break (usually ≤100% at -40℃), and even cracking of the bonding interface. At the same time, due to the instability of the cross-linked network structure, the adhesive is prone to thermal degradation in high temperature scenarios (such as the periphery of the automobile engine compartment, long-term operation of electronic devices), with a bonding strength retention rate of less than 60% at 100℃ or above, which cannot meet the long-term use requirements.

[0003] Weak moisture and heat aging resistance, poor long-term reliability In a humid and hot environment (such as the rainy season in the south, marine climate), the amide and urea bonds of existing polyurethane adhesives are prone to hydrolysis with water molecules, leading to the destruction of the cross-linked network. At the same time, water layers are easily formed at the interface between the substrate (such as metal, plastic) and the adhesive, weakening the interfacial adhesion. According to industry test data, the existing adhesives have a bonding strength decline rate of more than 20% after "50℃, 95% relative humidity (RH), 1000h" moisture and heat aging resistance test, and some products even completely debond, seriously affecting the service life of the equipment.

[0004] It is difficult to balance environmental protection and flame retardancy to meet the flame retardant requirements in the fields of electronics and automobiles (such as UL94 V-0 level, GB8410). Existing products mostly use halogen-based flame retardants (such as decabromodiphenyl ether), which have significant flame retardant effect, but release toxic and harmful gases (such as hydrogen bromide) during combustion, which does not meet the environmental protection standards such as EU ROHS and China GB / T30512. When using a single inorganic flame retardant (such as aluminum hydroxide, magnesium hydroxide), a large amount (mass ratio ≥30%) needs to be added to achieve the flame retardant grade, resulting in a significant decrease in the mechanical properties (such as tensile strength, flexibility) of the adhesive, and the aggregation of additives, affecting the appearance and workability.

[0005] The existing polyurethane adhesive has poor adaptability to different polar substrates: for polar substrates (such as metal, glass), the interfacial bonding force is weak due to the lack of strong polar groups (such as amino, epoxy); for non-polar substrates (such as polypropylene, polyethylene), it is difficult to wet and spread due to the large difference in surface energy, and pre-treatment such as polishing and coating primer is required, increasing the construction process and cost, and the bonding may fail due to improper pre-treatment.

[0006] In the existing preparation process, the control precision of the pre-polymerization temperature is insufficient (usually fluctuating ±5℃), which easily leads to incomplete reaction of isocyanate (NCO) and hydroxyl (OH), or the generation of by-products such as urea-based formic acid ester, resulting in a NCO content fluctuation of more than 1% in the pre-polymer; at the same time, functional additives (such as flame retardants, coupling agents) are mostly added directly, lacking a pre-dispersion process, resulting in uneven dispersion of the additives in the adhesive (particle size ≥5μm), with a mechanical property error of more than 15% between batches, affecting the consistency of industrial production.

[0007] To solve the above problems, some improvements have been tried in the industry (such as adding plasticizers to improve low-temperature toughness, using modified isocyanate to improve temperature resistance), but most of them are single performance optimization, and no synergistic solution has been formed for "wide temperature range - moisture and heat resistance - environmentally friendly flame retardant - universal bonding", and the preparation process lacks systematic optimization, making it difficult to realize industrialization. Therefore, it is an urgent need in the current high molecular adhesive field to develop a polyurethane adhesive that takes into account multiple performance dimensions, process stability and environmental protection, and a preparation method thereof. SUMMARY

[0008] (1) Technical problems solved To solve the problems of existing polyurethane adhesives, such as poor performance in wide temperature range, weak moisture and heat resistance, difficult to balance environmental protection and flame retardancy, insufficient substrate versatility, and poor preparation process stability, the present application provides a polyurethane adhesive and a preparation method thereof, which has the advantages of strong bonding stability in wide temperature range, high moisture and heat resistance, balanced environmental protection and flame retardancy, good substrate bonding versatility, and stable preparation process.

[0009] (II) Technical Solution The technical solution of the present application to solve the above technical problems is as follows: a polyurethane adhesive and a preparation method thereof, comprising the following components by mass fraction: high-activity polyoxypropylene-ethylene oxide copolymer polyol 85-125 parts, isocyanate mixture 28-40 parts, composite chain extender 6-12 parts, environmentally friendly catalyst 0.3-0.8 parts, phosphorus-nitrogen synergistic flame retardant 15-25 parts, anti-aging additive 0.8-1.5 parts, and silane coupling agent 1.2-2.0 parts. The preparation method comprises the following steps: S1, the high-activity polyoxypropylene-ethylene oxide copolymer polyol is added to a reaction kettle with stirring, temperature measurement and vacuum system, and dehydrated at 115-135℃, vacuum degree ≤-0.095MPa for 2-3h, until the moisture content of the material is ≤0.05%, and then cooled to 65-75℃; S2, slowly add the isocyanate mixture to the dehydrated polyol, control the drop rate at 1-2 drops per second, after the drop is completed, heat to 75-90℃, and react for 2.5-4h at a stirring speed of 300-400r / min to prepare polyurethane, the NCO mass fraction of the prepolymer is controlled at 6%-8%; S3: the composite chain extender, environmentally friendly catalyst, phosphorus-nitrogen synergistic flame retardant, anti-aging additive, and silane coupling agent are added to a high-speed dispersing machine, and dispersed at 50-60℃, 800-1000r / min for 30-50min to prepare a uniform composite functional additive; S4: the polyurethane prepolymer is cooled to 55-65℃, and the composite functional additive is uniformly added thereto, and stirred at 200-300r / min for 1-1.5h, during which the viscosity of the system is controlled at 3000-5000mPa・s at 25℃ by sampling every 20min; S5: the mixture in S4 is transferred to a sealed curing tank, and cured at 80-95℃, vacuum degree ≤-0.08MPa for 4-8h, and then cooled to room temperature and sealed and packaged to obtain the polyurethane adhesive.

[0010] The present application has the following advantages: Wide temperature range performance: elongation at break ≥220% at-40℃ (120% higher than existing products), adhesive strength retention rate ≥85% at 120℃, suitable for extreme temperature scenarios (such as northern outdoor, automobile engine compartment).

[0011] Wet heat aging strength: after 1000h test at 50℃, 95%RH, the strength retention rate is ≥92% (existing ≤80%), avoiding hydrolysis and debonding in a humid heat environment, prolonging the service life of the equipment.

[0012] Environment-friendly flame-retardant: flame-retardant reaches UL94V-0 level, flame-retardant additive amount is less than or equal to 20% (existing inorganic flame-retardant needs to be greater than or equal to 30%), tensile strength is greater than or equal to 18MPa;With environment-friendly catalyst, VOC is less than or equal to 12g / L, conforms to ROHS, GB / T30512.

[0013] General and efficient base material: no need to pretreat to stick aluminum alloy (greater than or equal to 18MPa), polypropylene (greater than or equal to 12MPa), glass (greater than or equal to 16MPa), construction efficiency is increased by 30%+, cost and failure risk are reduced.

[0014] Process stability: NCO content fluctuation of prepolymer is less than or equal to 0.2%, additive particle size is less than or equal to 2um, batch performance error is less than or equal to 7% (existing 15%), which meets industrial production.

[0015] The polyurethane adhesive and the preparation method thereof have the advantages of wide temperature range bonding stability, high wet heat aging performance, environment-friendly and flame-retardant characteristics, good general substrate bonding versatility and stable preparation process.

[0016] On the basis of the above technical scheme, the application can also be improved as follows.

[0017] Further, the mass fraction of ethylene oxide units in the high-activity polyoxypropylene-ethylene oxide copolymer polyol is 15% to 25%, the hydroxyl value is 80-120mgKOH / g, the number average molecular weight is 2000-4000g / mol, and the acid value is less than or equal to 0.1mgKOH / g.

[0018] The beneficial effects of the above further scheme are that the ethylene oxide segment can improve the polarity of the polyol and enhance the interfacial adhesion with polar substrates such as metals and glass; the copolymer structure can reduce the glass transition temperature (Tg) to below-50℃, greatly improving the low-temperature flexibility of the adhesive; the high hydroxyl value (80-120mgKOH / g) ensures rapid and sufficient reaction with isocyanate, reducing the generation of by-products; and the low acid value (less than or equal to 0.1mgKOH / g) can avoid the interference of acidic substances on the catalytic reaction, ensuring the stability of the system.

[0019] Further, the isocyanate mixture is composed of diphenylmethane diisocyanate MDI-50 and hexamethylene diisocyanate HDI at a mass ratio of 6-8:2-4, wherein the NCO mass fraction of MDI-50 is 30% to 32%, and the NCO mass fraction of HDI is 48% to 49%.

[0020] The beneficial effect of adopting the further scheme is that MDI-50 contains rigid benzene ring structure, which can improve the room temperature bonding strength and high temperature stability of the adhesive; HDI is aliphatic isocyanate, which can enhance the weather resistance and anti-yellowing performance of the adhesive; the two are compounded in a ratio of 6-8:2-4 to optimize the crosslinking network density, avoid the problem of hard segment aggregation (easy to be brittle) or soft segment excess (insufficient strength) caused by single isocyanate, and ensure that the prepolymerization is controllable by precisely controlling the NCO content (MDI-50 30%-32%, HDI 48%-49%).

[0021] Further, the composite chain extender is composed of a small molecule chain extender and a large molecule chain extender in a mass ratio of 1:2-3; the small molecule chain extender is 1,4-butanediol with a purity of more than 99.5%, and the large molecule chain extender is polybutylene adipate diol, which has a number average molecular weight of 1000-2000 g / mol and a hydroxyl value of 100-200 mgKOH / g.

[0022] The beneficial effect of adopting the further scheme is that high-purity 1,4-butanediol (≥99.5%) as a small molecule chain extender can quickly improve the crosslinking density of polyurethane, enhance the hardness and tensile strength of the adhesive, and the long chain structure of PBA as a large molecule chain extender can lengthen the soft segment length and improve the flexibility and elongation at break of the adhesive; the compounding ratio of 1:2-3 can balance the "hardness-flexibility" relationship and avoid the problems of "hard and brittle" caused by single small molecule chain extender or "soft and weak" caused by single large molecule chain extender, and the specific number average molecular weight (1000-2000 g / mol) and hydroxyl value (100-200 mgKOH / g) of PBA ensure the consistency of the chain extension reaction.

[0023] Further, the environmentally friendly catalyst is a compound of bismuth octoate Bi content ≥28% and N,N-dimethylcyclohexylamine in a mass ratio of 3-5:1, and the total amount of the catalyst is not more than 0.5% of the total mass of the adhesive.

[0024] The beneficial effect of adopting the further scheme is that bismuth octoate (Bi content ≥28%) replaces the traditional toxic tin catalyst, which meets the environmental protection standards of ROHS, GB / T30512, etc., and can gently catalyze the reaction of NCO and OH; N,N-dimethylcyclohexylamine as an amine catalyst can adjust the reaction rate to prevent the prepolymer from gelling due to too fast reaction; the compounding ratio of 3-5:1 can balance the environmental protection and reaction controllability, and the total amount of ≤0.5% can prevent the side reactions (such as urethane formation) caused by excessive catalyst, ensuring the stable performance of the adhesive.

[0025] Further, the phosphorus-nitrogen synergistic flame retardant is composed of phosphate and melamine cyanurate MCA in a mass ratio of 2-3:1, wherein the phosphorus content of TEPIC-P is ≥12%, and the nitrogen content of MCA is ≥49%.

[0026] The beneficial effect of the above further scheme is that TEPIC-P (phosphorus content ≥12%) forms a phosphate glass layer when burning, which can isolate oxygen and heat; MCA (nitrogen content ≥49%) releases inert gas (such as nitrogen) when burning, which dilutes the combustible gas, and the two form a synergistic effect of "physical isolation + gas flame retardation", so that the addition amount of the flame retardant is reduced to below 20% (much lower than ≥30% of a single inorganic flame retardant), avoiding the decrease of the mechanical properties of the adhesive; at the same time, the halogen-free composition ensures that no toxic gas is released during burning, and both flame retardation and environmental protection are considered.

[0027] Further, the anti-aging additive is composed of antioxidant 1010 and ultraviolet absorber UV-327 in a mass ratio of 2:1; the silane coupling agent is γ-aminopropyl triethoxysilane KH-550 or γ-glycidyl ether oxypropyl trimethoxysilane KH-560.

[0028] The beneficial effect of the above further scheme is that antioxidant 1010 can inhibit the free radical degradation of the adhesive at high temperature, and improve the thermal oxygen stability; UV-327 can absorb ultraviolet rays, avoiding yellowing and cracking of the adhesive due to light aging; 2:1 compounding can form a synergistic protection of "anti-thermal oxygen-anti-ultraviolet", prolonging the outdoor service life of the adhesive; the amino group / epoxy group at one end of KH-550 / KH-560 can react with the polyurethane group, and the ethoxyl group / methoxyl group at the other end can combine with the hydroxyl group on the surface of the substrate, eliminating the water layer at the interface, improving the moisture and heat aging resistance, and realizing universal bonding of metal, plastic and glass without pretreatment. BRIEF DESCRIPTION OF DRAWINGS

[0029] Figure 1 The preparation process of the present application is shown in the figure. DETAILED DESCRIPTION

[0030] The technical solutions in the embodiments of the present application will be described clearly and completely below with reference to the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative labor are within the scope of protection of the present application.

[0031] In the embodiments, the polyurethane adhesive is prepared by mixing the following components, Figure 1 The present application provides a polyurethane adhesive and a preparation method thereof. Specific embodiment 1: general-purpose polyurethane adhesive (adapted to metal / plastic / glass) 1. Component preparation (mass parts) High-activity polyoxypropylene-ethylene oxide copolymer polyol (ethylene oxide 20%, hydroxyl value 100 mg KOH / g) 100 parts; isocyanate mixture (MDI-50:HDI=7:3) 35 parts; composite chain extender (1,4-butanediol:PBA=1:2.5) 9 parts; environmentally friendly catalyst (bismuth isooctoate:N,N-dimethylcyclohexylamine=4:1) 0.5 parts; phosphorus-nitrogen synergistic flame retardant (TEPIC-P:MCA=2.5:1) 20 parts; anti-aging aid (antioxidant 1010:UV-327=2:1) 1.2 parts; silane coupling agent KH-550 1.5 parts.

[0032] 2. Preparation steps Step 1: Add polyol to the reaction kettle, dehydrate at 125°C and -0.095 MPa for 2.5 h, moisture ≤0.05%, cool to 70°C; Step 2: Add isocyanate mixture (1.5 drops / sec), heat to 85°C, stir at 350 r / min for 3 h, and detect NCO content of 7.0%; Step 3: Add composite chain extender, catalyst, flame retardant, anti-aging aid, and KH-550 to a high-speed disperser, disperse at 55°C and 900 r / min for 40 min, and particle size ≤2 μm; Step 4: Cool the prepolymer to 60°C, add the composite aid, and stir at 250 r / min for 1.2 h, and viscosity 4200 mPa・s (25°C); Step 5: Vacuum curing at 85°C and -0.09 MPa for 6 h, and package after cooling.

[0033] Performance test results Test item Test result Room temperature adhesive strength (aluminum alloy) 19.2 MPa Room temperature adhesive strength (polypropylene) 13.5 MPa Room temperature adhesive strength (glass) 17.8 MPa Elongation at break at -40°C 235% Adhesive strength retention rate at 120°C 87% Retention rate after humid heat aging (1000 h) 93% Flame retardant grade UL94 V-0 grade VOC content 11.8 g / L Strength error between batches 6.2% DETAILED DESCRIPTION 2: High-temperature-resistant polyurethane adhesive (adapted to automobile engine compartment) 1. Component preparation (mass parts) High-activity polyoxypropylene-ethylene oxide copolymer polyol (ethylene oxide 15%, hydroxyl value 120 mg KOH / g) 90 parts; isocyanate mixture (MDI-50:HDI=8:2) 38 parts; composite chain extender (1,4-butanediol:PBA=1:2) 8 parts; environmentally friendly catalyst (bismuth isooctoate:N,N-dimethylcyclohexylamine=5:1) 0.6 parts; phosphorus-nitrogen synergistic flame retardant (TEPIC-P:MCA=3:1) 22 parts; anti-aging aid (antioxidant 1010:UV-327=2:1) 1.5 parts; silane coupling agent KH-560 1.8 parts; modified nano-silicon dioxide (KH-570 treated) 2 parts.

[0034] 2. Preparation steps Step 1: Polyol + nano-silica into the reaction kettle, 130℃, -0.095MPa dehydration for 3h, cooling to 72℃; Step 2: drop isocyanate mixture (1.2 drops / sec), temperature to 90℃, 400r / min stirring reaction 3.5h, NCO content 7.5%; Step 3: composite chain extender, catalyst, flame retardant, anti-aging aid, KH-560 high-speed dispersion (1000r / min, 58℃) 45min; Step 4: prepolymer cooling to 62℃, adding composite aid, 300r / min stirring 1.5h, viscosity 4800mPa・s; Step 5: 90℃, -0.09MPa vacuum curing 7h, after cooling package.

[0035] 3. Performance test results Test item Test result Room temperature adhesive strength (aluminum alloy) 21.5 MPa Adhesive strength retention rate at 150°C 82% Elongation at break at -40°C 205% Taber abrasion amount (1000 times) 4.2 mg Flame retardant grade UL94 V-0 grade Retention rate after humid heat aging (1000 h) 91% DETAILED DESCRIPTION 3: Outdoor weather-resistant polyurethane adhesive (adapted to building curtain wall) 1. Component preparation (parts by mass) High-activity polyoxypropylene-ethylene oxide copolymer polyol (ethylene oxide 25%, hydroxyl value 80mgKOH / g) 120 parts; isocyanate mixture (MDI-50:HDI=6:4) 32 parts; composite chain extender (1,4-butanediol: PBA=1:3) 10 parts; environmentally friendly catalyst (bismuth isooctoate: N,N-dimethylcyclohexylamine=3:1) 0.4 parts; phosphorus-nitrogen synergistic flame retardant (TEPIC-P:MCA=2:1) 18 parts; anti-aging aid (antioxidant 1010: UV-327=2:1) 1.0 parts; silane coupling agent KH-550 1.6 parts; polycarbodiimide (PCD) 0.8 parts.

[0036] 2. Preparation steps Step 1: polyol into the reaction kettle, 120℃, -0.09MPa dehydration for 2h, cooling to 68℃ Step 2: drop isocyanate mixture (1.8 drops / sec), temperature to 80℃, 300r / min stirring reaction 2.8h, NCO content 6.8% (NCO / OH=1.1); Step 3: composite chain extender, catalyst, flame retardant, anti-aging aid, KH-550, PCD high-speed dispersion (800r / min, 52℃) 35min; Step 4: prepolymer cooling to 58℃, adding composite aid, 200r / min stirring 1h, viscosity 3800mPa・s; Step 5: 80℃, 700W microwave-assisted curing 2.5h, after cooling package.

[0037] 3. Performance test results Test item Test result Room temperature adhesive strength (glass-metal) 16.8 MPa Retention rate after xenon lamp aging (2000 h) 90% Retention rate after humid heat aging (1000 h) 96% Elongation at break at -40°C 250% VOC content 10.5 g / L Working principle: First step: synergistic construction of multifunctional crosslinking network: high-activity polyoxypropylene-ethylene oxide copolymer polyol provides low-temperature flexibility and polar adhesion, MDI-50 / HDI mixed isocyanate provides high-temperature stability and weather resistance, composite chain extender balances hardness and toughness, phosphorus-nitrogen synergistic flame retardant forms "insulation-dilution" dual flame retardant, anti-aging additives achieve "anti-thermal oxygen-anti-ultraviolet" protection, silane coupling agent bridges the adhesive and the substrate, and finally forms a "flexibility-strength-flame retardant-weather resistance-universal" integrated network.

[0038] Second step: precise process control of reaction process: "high temperature and high vacuum dehydration" (115-135°C, ≤-0.095MPa) removes polyol moisture to avoid bubble formation; "stepwise heating + precise dropwise addition" prepolymerization (1-2 drops / second, 75-90°C) ensures complete NCO reaction (content 6%-8%); "high-speed temperature-controlled dispersion" of additives (800-1000r / min, 50-60°C) ensures particle size ≤2μm without agglomeration; "vacuum curing" (80-95°C, ≤-0.08MPa) promotes densification of the crosslinking network and removes residual small molecules.

[0039] Third step: synergistic effect solves technical pain points: the combination of multifunctional network and precise process not only improves the performance of wide temperature range, moisture resistance, flame retardance, etc., but also realizes the universality of the substrate and batch stability, ultimately meeting the bonding needs of high-end fields such as automobiles, electronics, and construction, and meeting the requirements of environmental protection and industrial production.

[0040] It should be noted that, in this text, relational terms such as first and second are used merely to distinguish one entity or action from another, and do not necessarily require or imply that there is any such actual relationship or order between these entities or actions. Moreover, the terms "include", "contain" or any other variant thereof are intended to cover non-exclusive inclusion, so that the process, method, article or equipment including a series of elements not only includes those elements, but also includes other elements not explicitly listed or inherent to such process, method, article or equipment. Without more limitations, the element defined by the statement "including a…" does not exclude the presence of additional identical elements in the process, method, article or equipment that includes the element.

[0041] Although embodiments of the present application have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the present application, and the scope of the present application is defined by the appended claims and their equivalents.

Claims

1. A polyurethane adhesive, characterized in that: It comprises the following components in parts by weight: 85-125 parts of highly active polypropylene oxide-ethylene oxide copolymer polyol, 28-40 parts of isocyanate mixture, 6-12 parts of composite chain extender, 0.3-0.8 parts of environmentally friendly catalyst, 15-25 parts of phosphorus-nitrogen synergistic flame retardant, 0.8-1.5 parts of aging resistant additive, and 1.2-2.0 parts of silane coupling agent.

2. The polyurethane adhesive according to claim 1, characterized in that: The highly active polypropylene oxide-ethylene oxide copolymer polyol has an ethylene oxide unit mass ratio of 15% to 25%, a hydroxyl value of 80-120 mgKOH / g, a number average molecular weight of 2000-4000 g / mol, and an acid value ≤0.1 mgKOH / g.

3. The polyurethane adhesive according to claim 1, characterized in that: The isocyanate mixture is composed of diphenylmethane diisocyanate MDI-50 and hexamethylene diisocyanate HDI in a mass ratio of 6-8:2-4, wherein the NCO mass fraction of MDI-50 is 30% to 32% and the NCO mass fraction of HDI is 48% to 49%.

4. The polyurethane adhesive according to claim 1, characterized in that: The composite chain extender is composed of a small molecule chain extender and a large molecule chain extender in a mass ratio of 1:2-3; the small molecule chain extender is 1,4-butanediol with a purity of 99.5% or higher, and the large molecule chain extender is polybutylene adipate diol, which has a number average molecular weight of 1000-2000 g / mol and a hydroxyl value of 100-200 mg KOH / g.

5. The polyurethane adhesive according to claim 1, characterized in that: The environmentally friendly catalyst is a compound of bismuth isooctanoate (Bi content ≥ 28%) and N,N-dimethylcyclohexylamine in a mass ratio of 3-5:1, and the total amount of catalyst used does not exceed 0.5% of the total mass of the adhesive.

6. The polyurethane adhesive according to claim 1, characterized in that: The phosphorus-nitrogen synergistic flame retardant is composed of phosphate ester and melamine cyanurate (MCA) in a mass ratio of 2-3:1, wherein the phosphorus content of TEPIC-P is ≥12% and the nitrogen content of MCA is ≥49%.

7. The polyurethane adhesive according to claim 1, characterized in that: The anti-aging additive is composed of antioxidant 1010 and ultraviolet absorber UV-327 in a mass ratio of 2:1; the silane coupling agent is γ-aminopropyltriethoxysilane KH-550 or γ-glycidoxypropyltrimethoxysilane KH-560.

8. A method for preparing a polyurethane adhesive, characterized in that, The preparation of the polyurethane adhesive as described in claim 1 comprises the following steps: S1. Add the highly active polyoxypropylene-ethylene oxide copolymer polyol to a reactor equipped with a stirring, temperature measuring and vacuum system, and dehydrate it for 2-3 hours at 115-135℃ and vacuum degree ≤-0.095MPa until the moisture content of the material is ≤0.05%, and then cool it down to 65-75℃. S2. Slowly add the isocyanate mixture to the dehydrated polyol, controlling the dropping rate to 1-2 drops per second. After the addition is complete, raise the temperature to 75-90℃ and react with a stirring speed of 300-400 r / min for 2.5-4 h to obtain the polyurethane prepolymer. The NCO mass fraction of the polyurethane prepolymer is controlled at 6%-8%. S3: Add the composite chain extender, environmentally friendly catalyst, phosphorus-nitrogen synergistic flame retardant, aging resistant agent and silane coupling agent to a high-speed disperser and disperse for 30-50 minutes at 50-60℃ and 800-1000r / min to obtain a uniform composite functional additive. S4: Cool the polyurethane prepolymer to 55-65℃, add the composite functional additives at a uniform rate, and stir at 200-300r / min for 1-1.5h. During this period, take a sample every 20min to test the viscosity of the system, which should be controlled at 3000-5000mPa・s at 25℃. S5: Transfer the mixture from S4 to a sealed curing tank and cure it at 80-95℃ and a vacuum degree ≤-0.08MPa for 4-8 hours. After cooling to room temperature, seal and package it to obtain the polyurethane adhesive.